Genome-wide association study identifies ABCG1 as a susceptibility locus for tick-borne encephalitis - Gampawar, Piyush G; Sagmeister, Manfred G; Růžek, Daniel; Schweintzger, Nina A; Hofer, Edith; Kohlmaier, Benno; Švendová, Vendula; Bogovič, Petra; Zajkowska, Joanna M; Krbková, Lenka; Štruncová, Věra; Mickienė, Auksė; et al. (iScience, 2025)
Tick-borne encephalitis (TBE) is a viral infection of the central nervous system, caused by the tick-borne encephalitis virus (TBEV) presenting clinically as meningitis, meningoencephalitis, and meningoencephalomyelitis. To investigate genetic susceptibility to TBE, and its severe forms, we conducted a genome-wide association study in the European population comprising 1,600 TBE cases and 9,699 controls. We identified several suggestive (p < 1 × 10-5) intronic and exonic variants in ABCG1, the only gene significantly associated with TBE susceptibility. These variants were shown to influence ABCG1 expression in peripheral blood, a finding corroborated by RNA expression analysis. In vitro inhibition or silencing of ABCG1 significantly reduced TBEV replication in both neuronal cells and macrophages, highlighting the potential role of ABCG1 in TBEV biology. Additionally, we detected a genome-wide significant variant within TEX41, located downstream of ZEB1, associated with severe forms of TBE. These findings provide novel insights into the genetic factors underlying TBE susceptibility and severity.
Keywords: Genetics; Microbiology; Bioinformatics